Tenofovir Disoproxil Fumarate - Joel E. Gallant; Stan Deresinski (2003)
Tenofovir disoproxil fumarate (tenofovir DF) is a bioavailable prodrug of tenofovir, a potent nucleotide analogue reverse-transcriptase inhibitor with activity against human immunodeficiency virus (HIV) and hepatitis B virus. It is administered as a single 300-mg tablet once daily. It was approved for the treatment of HIV infection on the basis of data from clinical trials demonstrating activity in treatment-experienced patients, and it was subsequently shown to be effective when used as a component of initial therapy. Tenofovir DF is active against some nucleoside-resistant strains of HIV. However, cross-resistance is associated with multiple thymidine analogue mutations that include 41L or 210W. The signature mutation is the K65R mutation, which causes variable loss in susceptibility to tenofovir DF, didanosine, and abacavir. Tenofovir DF has been well tolerated in clinical trials with durations of follow-up up to 96 weeks. It is associated with more-favorable lipid profiles than stavudine and has not been associated with the mitochondrial toxicity attributed to other nucleoside analogues.